(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This in the thesis Japan education​​ system history , development trends , monitoring the further activities of teachers importance and his/her to oneself typical features , in Uzbekistan Japan from experience used without education​​ system , including general​ middle​​ education​​ reform to do issues statement Made in Japan the mechanism of the formation and development of the education system scientific the basics open to give with related issues analysis done.